2022
DOI: 10.21203/rs.3.rs-1826997/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical outcome of drug-coated balloons in patients with femoropopliteal chronic total occlusive lesions: results from the multicenter EAGLE study

Abstract: Background: Several studies have reported the efficacy of drug-coated balloons (DCB) for simple femoropopliteal (FP) lesions. However, the effectiveness of DCB for FP chronic total occlusive lesions (CTO) is controversial. The present study investigated the clinical outcomes of DCB for FP-CTO.Materials and methods: We retrospectively analyzed 359 limbs of 318 patients who underwent EVT with DCB for FP-CTO between July 2017 and February 2021 at seven cardiovascular centers. The primary endpoint was 12-month pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The main findings in the present study are as follows: (1) the 1‐year primary patency rate and freedom from CD‐TLR were 79.3% and 82.4%, respectively; (2) the predictors of 1‐year restenosis were the lack of cilostazol, P3 segment involvement, and small RVD; (3) all‐cause mortality, major amputation, and CD‐TLR were observed in 9.7%, 1.8%, and 13.3%, respectively, of the whole population at 1 year. The previous registries demonstrated that poor primary patency was associated with conservative antiplatelet therapies, involvement of popliteal segments and small vessel disease 7,8,17,18 ; however, these studies included patients with relatively short FP lesions (mean length ranged from 8.4 to 21.9 cm). Our study highlighted that the importance of the classical risk factors was consistent in extremely diffuse FP lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main findings in the present study are as follows: (1) the 1‐year primary patency rate and freedom from CD‐TLR were 79.3% and 82.4%, respectively; (2) the predictors of 1‐year restenosis were the lack of cilostazol, P3 segment involvement, and small RVD; (3) all‐cause mortality, major amputation, and CD‐TLR were observed in 9.7%, 1.8%, and 13.3%, respectively, of the whole population at 1 year. The previous registries demonstrated that poor primary patency was associated with conservative antiplatelet therapies, involvement of popliteal segments and small vessel disease 7,8,17,18 ; however, these studies included patients with relatively short FP lesions (mean length ranged from 8.4 to 21.9 cm). Our study highlighted that the importance of the classical risk factors was consistent in extremely diffuse FP lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to evaluate the safety and efficacy of the contemporary EVT using the latest devices in patients with symptomatic PAD having FP lesions longer than 25 cm in clinical practice. In addition, several studies indicated that medical treatment might be helpful to keep patency after revascularization such as antiplatelet therapy, cilostazol and oral anti‐coagulation; therefore, anti‐thrombotic therapies can play an important role in the current EVT era 7–9 . We investigated the associated factors to improve the vessel patency, which included patent and lesion background, EVT devices and medical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation